2014
DOI: 10.1016/j.gynor.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Familial HCG syndrome: A diagnostic challenge

Abstract: HighlightsThis is a rare inheritable condition which results in raised total HCG levels.Common causes of raised HCG need to be excluded prior to considering this syndrome.A diagnosis can prevent unnecessary surgical or oncological treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…58,59 In familial hCG syndrome, nonpregnant male and female individuals produce a mutated form of hCG with alteration in the C-terminal peptide region of the molecule. 58,59 This production outside of pregnancy or malignancy results in a persistently elevated hCG level. 59 The site of origin of this mutated hCG is unknown.…”
Section: False Positivesmentioning
confidence: 99%
See 1 more Smart Citation
“…58,59 In familial hCG syndrome, nonpregnant male and female individuals produce a mutated form of hCG with alteration in the C-terminal peptide region of the molecule. 58,59 This production outside of pregnancy or malignancy results in a persistently elevated hCG level. 59 The site of origin of this mutated hCG is unknown.…”
Section: False Positivesmentioning
confidence: 99%
“…59 The site of origin of this mutated hCG is unknown. 58 One case study of 15 cases found that in each case the syndrome was confirmed by either a parent or sibling also exhibiting ectopic hCG production. 60 Individuals with familial hCG syndrome can experience false diagnoses of ectopic pregnancy or malignancy, with subsequent unnecessary workup and treatment.…”
Section: False Positivesmentioning
confidence: 99%
“…49 Affected patients produce hCG moieties that contain multiple CTP modifications that lead to persistently elevated hCG assay results. 50 The hCG present in journals.sagepub.com/home/reh Therapeutic Advances in Reproductive Health 15 familial hCG syndrome is thought to lack the betasubunit C-terminus or have a mutated CTP region. Such hCG molecules with modified CTPs usually have gone undetected because a majority of hCG assays (11 out of 12) cannot detect hCG molecules that are missing the B subunit CTP region.…”
Section: Phantom Hcg Syndromementioning
confidence: 99%
“…Extraplacental secretion of hCG in small amounts occurs in the liver and colon 14 and in familial hCG syndrome. 15 Measurements of urine or serum hCG levels are mandatory, before any routine or emergent medical and surgical procedures, even in women of perimenopausal age. The assumption that elevated hCG outside of pregnancy is always pathologic has led to potentially harmful and unwarranted interventions or delaying necessary medical interventions for women.…”
Section: Introductionmentioning
confidence: 99%